Technology for Teaching Free Mechanical Vibration Graphics in Microsoft Excel Software - M.B.Dusmuratov; L.Y.Turayeva (Genius Journals, 2022)
In this article, harmonic oscillations of a mathematical and spring pendulum are considered, and graphs of the dependence of speed and acceleration on time and coordinates were obtained using the Microsoft Excel software tool.
Keywords: The equation of motion; velocity; acceleration; amplitude